2008
DOI: 10.1002/pssc.200778586
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence properties of GaPN layer grown by OMVPE

Abstract: The effect of carbon incorporation on luminescence properties of GaPN grown by organometallic vapor phase epitaxy (OMVPE) has been investigated. Trimethylgallium (TMGa) and trimethylgallium (TEGa) were used as Ga precursors. The carbon concentration of 1.1×1017cm–3 was obtained by using TEGa, whereas that of GaPN grown using TMGa was 4.0×1017cm–3. Non‐radiative recombination rate was also reduced to about 1/100 by using TEGa. Moreover, the spatial fluctuation of N content and Non‐radiative rate was reduced wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…3 shows N-content dependence of carrier concentration and mobility in C-doped GaP(N). The carrier concentration at first increased with N incorporation, as expected from the positive dependence of C concentration on N incorporation (DMHy flow rate) [6]. However, the carrier concentration was found to decrease for N-content above 1%, although C concentration increased.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…3 shows N-content dependence of carrier concentration and mobility in C-doped GaP(N). The carrier concentration at first increased with N incorporation, as expected from the positive dependence of C concentration on N incorporation (DMHy flow rate) [6]. However, the carrier concentration was found to decrease for N-content above 1%, although C concentration increased.…”
Section: Resultsmentioning
confidence: 69%
“…In the growth of GaPN, Geisz et al [9] has been reported that C is unintentionally incorporated from organometallic sources (TEGa and DMHy) in OMVPE-grown GaPN and it acts as acceptor. In particular, DMHy is the major origin of C incorporation in GaPN at growth temperature of 600 1C [6]. Therefore, C-doped p- GaPN ratio was controlled to stabilize the N-content of C-doped p-GaPN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation